2013
DOI: 10.1158/1078-0432.ccr-12-3588
|View full text |Cite
|
Sign up to set email alerts
|

DNA Demethylating Agents Synergize with Oncolytic HSV1 against Malignant Gliomas

Abstract: Purpose Oncolytic viruses (OV) based on herpes simplex virus type 1 (HSV1) are being utilized in clinical trials for a variety of cancers. The OV, rQNestin34.5, utilizes a nestin promoter/enhancer to selectively drive robust viral replication in malignant glioma cells. We have discovered that this promoter becomes extensively methylated in infected glioma cells, reducing OV efficacy. Experimental Design We utilized demethylating drugs (5-azacytidine), Decitabine or Valproic Acid (VPA) in both in vitro and in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…Studies combining OVs with epigenetic modifiers such as 5-Aza have shown synergistic or additive effects that enhance tumor cell death. 23–25 To ensure that 5-Aza was functional in LCRT cells, the expression of Dnmt1 was evaluated as a control. When incorporated into DNA, 5-Aza forms a covalent bond with DNMT such as Dnmt1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies combining OVs with epigenetic modifiers such as 5-Aza have shown synergistic or additive effects that enhance tumor cell death. 23–25 To ensure that 5-Aza was functional in LCRT cells, the expression of Dnmt1 was evaluated as a control. When incorporated into DNA, 5-Aza forms a covalent bond with DNMT such as Dnmt1.…”
Section: Resultsmentioning
confidence: 99%
“… 35 Epigenetic modifiers enhance OV replication and cytotoxicity by modifying viral gene expression and antiviral immune responses. 23–25 In addition to upregulating genes associated with innate and adaptive immunity, 5-Aza increases the sensitivity of tumor cells to T cell mediated cytotoxicity by increasing expression of TAAs. 36 , 37 Enhanced immune activation following 5-Aza treatment may serve to break central and peripheral tolerance to TAAs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kambara et al[ 51 ] developed an oncolytic HSV-1 mutant rQNestin34.5 which expresses ICP-34.5 under control of a synthetic nestin promoter. Nestin is expressed in embryonic neuroglial cells and has been used as a CSC marker in several cancers including brain tumors, and rQNestin34.5 showed significantly more potent inhibition of tumor growth compared with control virus in vivo [ 52 ]. Further studies found that rQNestin34.5 can infect and kill neuroblastoma CSCs[ 9 ], implying that OncoHSV efficiently targets CSCs from gastrointestinal cancer.…”
Section: Oncolytic Virotherapymentioning
confidence: 99%